Assessment of Muscle Activity During a Deadlift Performed by Construction Workers - Renato Alexandre da Costa-Machado; Ana Conceição; Fernando Rocha; Marco Branco (Muscles)
Construction work is physically demanding. The tasks involved in this professional occupation physically exhaust workers and put them at high risk of injury. This work aimed to analyze muscle fatigue in civil construction workers with and without a history of physical activity. For this purpose, the muscle activity of the biceps femoris, trapezius transversalis, and erector spinae longissimus muscles was evaluated using surface electromyography. Eleven male civil construction workers aged 26 to 52 years (38.00 ± 9.60), seven of whom were untrained (N = 7) and four of whom were trained (N = 4), participated in this study. Each subject completed two assessments at two different times. A questionnaire was completed for the first assessment, and each subject’s maximum repetition for the deadlift exercise was assessed. In the second assessment, the subjects were assessed while performing the deadlift in four different situations: 50%RM at rest, 70%RM at rest, 70%RM at fatigue, and 50%RM at fatigue. The trained construction workers had higher levels of muscle activity, and there were no significant differences in muscle activation between the fatigued and non-fatigued sets. There appears to be a strong influence of physical exercise on muscle activity and fatigue in civil construction workers.